Adhesion Control Logic Analysis of Domestic Traction Trains in Guangzhou Metro Third-northern Line - FAN Jiafeng; HE Wenle; ZHAO Renlong (机车电传动)
The application characteristics of adhesion control logic in 120 km/h domestic traction metro trains of Guangzhou metro third-northern line were introduced. Compared with the Siemens train, domestic traction train adhesion control was more outstanding in safety and rigor. Based on wheel-track adhesion characteristics, train antiskid control logic was analyzed emphatically, including skid detection and moment unloading/recovery logic. Test shows that the train antiskid control logic of the project can detect the skid phenomenon effectively and adjust the moment in time, which improves adhesion control performance greatly.